Test of Acceptance and Iron Content of Dimsum "Lori" as an Alternative Snack to Prevent Anemia in Adolescent Girls - Rena Vionita Ardana; Ani Intiyati; Nur Hatijah; Taufiqurrahman; Fahmi Hafid; Shivania Kathiresan (Journal of Nutrition Explorations, 2024)
Anemia is a problem today, if it’s not treated it will have a bad effect. Anemia can be prevented by consuming animal protein foods that are high iron content, namely anchovies with a content of 3.9mg/100g and vegetables that have a high in iron content, namely Moringa leaves. The aim is to determine the acceptability and iron levels of Dimsum Lori as an alternative snack to prevent anemia for Adolescents Girls. Methods, experimental research. There are 3 formulations, namely the formulation ratio between chicken meat: anchovy: moringa leaf flour, namely 100g:0g:0g, 0g:97g:3g, 0g:94g:6g. Acceptance test as many as 25 people, somewhat trained category. Test for iron levels, ICP-OES method. Data analysis technique, Kruskal Wallis statistical test and continued with the Man Whitney test. Research results, acceptability test F1; 3.86 (likes), F2; 3.37 (likes), and F3; 3.03 (regular). The results of the iron content test of the control formulation; 1.96mg/100g. Meanwhile, the most preferred formulation; 2.32mg/100g. In conclusion, the dimsum treatment formulation meets the needs of Fe in one snack of 2.3mg (F2); 2.5mg (F3) of the RDA requirement for Adolescents Girls for one snack of 1.27mg.